Frequency-domain synthetic aperture focusing for helical ultrasonic imaging - Jin, H. (2017)
The synthetic aperture focusing technique (SAFT) is widely used to provide significant improvement in the lateral resolution of ultrasonic images. Frequency-domain SAFT has shown higher accuracy and greater efficiency than time-domain SAFT. However, frequency-domain SAFT should be helix-based for ultrasonic scanning of cylindrical structures such as pipes and axletrees. In this study, a frequency-domain SAFT is proposed for 3D helical ultrasonic imaging applications. This technique adjusts the phase spectra of the images to complete the synthetic aperture focusing process. The focused image is precise because the proposed algorithm is established on the basis of the wave equation in a helical coordinate system. In addition, the algorithm can efficiently separate out point scatterers and present volume scatterers. The experimental results show that the proposed algorithm yields lower side lobes and enhances the angular resolution of the ultrasonic image to approximately 1°– 1.5°, which is much better than the performance of time-domain SAFT. The maximum deviations are only 0.6 mm, 0.5°, and 0.4 mm along the r-axes, θ-axes, and z-axes, respectively, which are appropriate for normal ultrasonic nondestructive testing.